Análise do uso integrado de eletrofloculador contínuo e coluna filtrante quanto à eficiência de remoção de óleo emulsionado em água - Oliveira, Odilon Junio Gonçalves de (2022)
Inadequate management of oily waste causes great environmental pollution in several ecosystems, mainly in aquatic pollution. Many of the conventional methods of separating contaminating oils are expensive and inefficient to remove. Increasingly, the industry needs waste treatment methods that allow the removal of higher percentages of contaminants from effluents. Through the use of a biosorbent, part of these problems can be overcome. Calotropis procera is a plant originally from India and commonly found in some regions of Brazil. Its fruit produces a fiber with oleophilic characteristics, in this way, a filtering column was assembled with the fiber of Calotropis procera as filling. This work aimed to study the efficiency of removing emulsified oil in water through the electroflocculation process associated with the use of this in natura vegetable fiber as a filter element to retain part of the contaminating oily residue. The synthetic effluent was exposed to the electroflocculation process, where aluminum plate electrodes were used as anode and cathode. In this study it was possible to observe that the fiber of Calotropis procera showed to be favorable to the biosorption of flocculated material and oily residue. During the experimental procedures, some of the variations in effluent characteristics were studied, reaching maximum TOG removal results at 97,34 ± 0.62 %, turbidity at 99,56 ± 0,19%, and COD at 93,86 ± 1,0%. In addition, the energy consumption during the treatment process was evaluated, which, adding the consumption by the reactor and the peristaltic pump, varied between 2,24 kWh.m³ at the lowest flow (2 mL.s-1 ) and 0,99 kWh.m³ at the highest flow rate (6 mL.s-1 ). Thus, it was possible to analyze the feasibility of associating the methods, and the use of the filter column with the vegetable fiber provided a lower energy consumption by enabling the treatment of a greater volume of effluent, reaching in the end an average reduction of 55,8 % in the electricity consumption, and 69,69% in the cost of operation when compared to the removal values of the post-reactor samples. The most adequate treatment condition was obtained with the application of Q = 6 mL.s-1 and Tinv = 20 s.